Novel Methods of Lymph Node Evaluation for Predicting the Prognosis of Colorectal Cancer Patients with Inadequate Lymph Node Harvest - Kwon, Taek Soo (Cancer Res Treat, 2016)
PURPOSE: Lymph node metastasis is an important factor for predicting the prognosis of colorectal cancer patients. However, approximately 60% of patients do not receive adequate lymph node evaluation (less than 12 lymph nodes). In this study, we identified a more effective tool for predicting the prognosis of patients who received inadequate lymph node evaluation. MATERIALS AND METHODS: The number of metastatic lymph nodes, total number of lymph nodes examined, number of negative metastatic lymph nodes (NL), lymph node ratio (LR), and the number of apical lymph nodes (APL) were examined, and the prognostic impact of these parameters was examined in patients with colorectal cancer who underwent surgery from January 2004 to December 2011. In total, 806 people were analyzed retrospectively. RESULTS: In comparison of different lymph node analysis methods for rectal cancer patients who did not receive adequate lymph node dissection, the LR showed a significant difference in overall survival (OS) and the APL predicted a significant difference in disease-free survival (DFS). In the case of colon cancer patients who did not receive adequate lymph node dissection, LR predicted a significant difference in DFS and OS, and the APL predicted a significant difference in DFS. CONCLUSION: If patients did not receive adequate lymph node evaluation, the LR and NL were useful parameters to complement N stage for predicting OS in colon cancer, whereas LR was complementary for rectal cancer. The APL could be used for prediction of DFS in all patients.